When Distress Becomes Somatic: Dementia Family Caregivers' Distress and Genetic Vulnerability to Pain and Sleep Problems. (23rd November 2018) - Wilson, Stephanie J; Padin, Avelina C; Birmingham, Daniel J; Malarkey, William B; Kiecolt-Glaser, Janice K
Abstract: Background and Objectives: Stress can trigger physical pain and disturb sleep. Whether dementia family caregivers experience heightened pain is unknown. Cycles of unwanted thoughts about caregiving stressors and avoidance of these thoughts—that is, caregiving-related distress—may exacerbate both pain and sleep disturbances, and genetic susceptibility to stress may further modulate these associations. Research Design and Methods: Dementia caregivers (72 spouses, 58 adult children, ages 34–89) rated the extent to which they experienced unintended thoughts about caregiving and tried to suppress such thoughts. They also reported their pain levels, sleep problems, and depressive symptoms. Peripheral blood leukocytes were genotyped for 5-HTTLPR (serotonin-transporter-linked polymorphic region) and 5-HT1A receptor polymorphism rs6295 on the 5HTR1A locus. Results: Short-allele carriers for 5-HTTLPR experienced more pain and sleep problems in association with greater caregiving-related distress than those with other genotypes. For rs6295, C carriers also showed the strongest links between distress and sleep problems. Those who experienced more avoidance and intrusive thoughts about caregiving had more severe depressive symptoms, consistent with past work. Discussion and Implications: Caregivers' genetic profiles helped to explain whether caregiving-related distress predicted worse pain and sleep problems. These data reveal new somatic risks of caregiver distress and provide targets for intervention. According to plasticity theories, caregivers genetically predisposed to greater stress reactivity may also respond particularly well to interventions, and many brief treatments may effectively address caregivers' intrusions and avoidance.